1987
DOI: 10.1210/endo-120-5-1719
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone-Releasing Factor-44 Specificity for Components of Somatotroph and Lactotroph Immediate Release Pool Substructures*

Abstract: Rat somatotroph and lactotroph hormone storage is divisible into at least two functional compartments: an immediate release pool (IRP) and a pool that responds to prolonged stimulation. An IRP substructure has been defined by release in response to potassium ion (K+), prostaglandin E1 (PGE1), and Bu2cAMP. The somatotroph IRP is expandable; the lactotroph IRP is fixed in size. The present experiments examined which IRP components contribute to the rapid release of stored GH in response to GH-releasing factor-44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Moreover, the replenishable GH pool model is obligatory to simulate post-SRIF rebound release of GH in the female formulation, wherein GH autofeedback is attenuated. Both projected outcomes agree with experimental data in the adult rat (37,42,45,46). And, third, systemic exposure to SRIF inhibits GH secretion, which in the present construct limits endogenous SRIF restraint and (on SRIF withdrawal) induces rebound-like GH release.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Moreover, the replenishable GH pool model is obligatory to simulate post-SRIF rebound release of GH in the female formulation, wherein GH autofeedback is attenuated. Both projected outcomes agree with experimental data in the adult rat (37,42,45,46). And, third, systemic exposure to SRIF inhibits GH secretion, which in the present construct limits endogenous SRIF restraint and (on SRIF withdrawal) induces rebound-like GH release.…”
Section: Discussionsupporting
confidence: 84%
“…Individual peptide elimination rates are assumed to be distinct and stable. The primary network-like connections (and their experimental derivation) are 1) GHRH's acute stimulation of GH release from somatotrope cells (8,18,26,30,37,42,43,45,46), 2) SRIF's antagonism of GHRHinduced GH secretion (18,20,34,42), 3) GH's delayed feedforward on SRIF release (6,9,29,31,34,35,37), 4) SRIF's inhibition of GHRH secretion (8,12,16,24,30), 5) GH's repression of GHRH outflow (7,9,16,31,32), 6) GHRH's time-lagged induction of pituitary SRIF secretion (1, 2, 11, 24, 27, 29, 32-34, 37, 46), and 7) GHRH's induction of the de novo synthesis and accumulation of (releasable) GH in the pituitary gland (20,34,42,45,46). This ensemble formulation extends an earlier basic construct by including intrahypothalamic GHRH-evoked SRIF outflow and GHRH-stimulated synthesis and accumulation of GH stores (see DISCUS-SION).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In those experim ents we also showed that sim ulta neous exposure to com bined SRIF and BuicAMP resulted in a rate of GPI release that was indistinguishable from the basal release rate [26]; in terms of net horm one release, these two secretagogues, therefore, cancelled each other's effects. We suggested a mechanism for the progressive seq uestration o f the intracellular horm one that is released after SRIF withdrawal [26,29,30] and supported the suggestion with an electron microscopic dem onstration of a juxtam embrane granule pool [27].…”
supporting
confidence: 55%
“…Part of newly synthesized GH was immediately released, and most of the newly synthesized GH was stored as secretory granules in the cytoplasm [Stachura and Tyler, 1987]. It is not clear that this may be dependent upon either the existence of separate intracellular pathways for the release and storage of GH, or the presence of functionally specialized subsets of GH cells within heterogeneous GH cell population.…”
Section: Discussionmentioning
confidence: 99%